Electronic monitoring of adherence to inhaled corticosteroids: an essential tool in identifying severe asthma in children. Issue 6 (21st December 2017) - Jochmann, Anja; Artusio, Luca; Jamalzadeh, Angela; Nagakumar, Prasad; Delgado-Eckert, Edgar; Saglani, Sejal; Bush, Andrew; Frey, Urs; Fleming, Louise J.
International guidelines recommend that severe asthma can only be diagnosed after contributory factors, including adherence, have been addressed. Accurate assessment of adherence is difficult in clinical practice. We hypothesised that electronic monitoring in children would identify nonadherence, thus delineating the small number with true severe asthma. Asthmatic children already prescribed inhaled corticosteroids were prospectively recruited and persistence of adherence assessed using electronic monitoring devices. Spirometry, airway inflammation and asthma control were measured at the start and end of the monitoring period. 93 children (62 male; median age 12.4 years) were monitored for a median of 92 days. Median (range) monitored adherence was 74% (21–99%). We identified four groups: 1) good adherence during monitoring with improved control, 24% (likely previous poor adherence); 2) good adherence with poor control, 18% (severe therapy-resistant asthma); 3) poor adherence with good control, 26% (likely overtreated); and 4) poor adherence with poor control, 32%. No clinical parameter prior to monitoring distinguished these groups. Electronic monitoring is a useful tool for identifying children in whom a step up in treatment is indicated. Different approaches are needed in those who are controlled when adherent or who are nonadherent. Electronic monitoring is essential in a paediatric severe asthma clinic. Children with true, severe therapy-resistant asthma cannot be identified without electronic adherence monitoring http://ow.ly/RMoU30fk1wu